Married, Older, Richer, and Better - Educated People are Happier in India - Pillania, Rajesh K. (Prabandhan: Indian Journal of Management, 2021)
There is increasing interest in happiness and its various aspects in the world and also in India. Though there is a big research gap in the pan - Indian context on the correlations of happiness with some important parameters, namely gender, marital status, age, education, and income, this study tried to fill this gap. The findings showed that income levels, marital status, education, and age group – all were positively related to happiness. Practitioners, namely, policymakers and corporate executives, need to consider these significant insights to understand people and what makes them happy. Instead of working on guesswork on what makes people happy, these insights on correlations of happiness are a good starting point for understanding people. Researchers and academicians can use these new findings in the Indian context as inputs in their research, teaching, and consultancy. One limitation of the study is that it explained the correlations of happiness. Cause and effect is a better measure, and future studies can focus on the causes and effects of happiness.